2023
DOI: 10.1101/2023.12.06.570482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The vestibulospinal nucleus is a locus of balance development

Kyla R. Hamling,
Katherine Harmon,
Yukiko Kimura
et al.

Abstract: Mature vertebrates maintain posture using vestibulospinal neurons that transform sensed instability into reflexive commands to spinal motor circuits. Postural stability improves across development. However, due to the complexity of terrestrial locomotion, vestibulospinal contributions to postural refinement in early life remain unexplored. Here we leveraged the relative simplicity of underwater locomotion to quantify the postural consequences of losing vestibulospinal neurons during development in larval zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(171 reference statements)
0
2
0
Order By: Relevance
“…Hindbrain VS neurons, which directly innervate trunk motor neurons, have decreased neuronal activity in mutants. Recently it was shown that ablation of VS neurons leads to modest defects in posture in zebrafish larvae [98], suggesting that other vestibular circuits contribute to postural control. The reduced activation of the vestibulospinal pathway in vps4a T248I mutants may therefore only partially account for the inability to maintain an upright posture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hindbrain VS neurons, which directly innervate trunk motor neurons, have decreased neuronal activity in mutants. Recently it was shown that ablation of VS neurons leads to modest defects in posture in zebrafish larvae [98], suggesting that other vestibular circuits contribute to postural control. The reduced activation of the vestibulospinal pathway in vps4a T248I mutants may therefore only partially account for the inability to maintain an upright posture.…”
Section: Discussionmentioning
confidence: 99%
“…Hindbrain VS neurons, which directly innervate trunk motor neurons, have decreased neuronal activity in mutants. Recently it was shown that ablation of VS neurons leads to modest defects in posture in zebrafish larvae [98],…”
Section: Sensory and Motor Deficitsmentioning
confidence: 99%